Privacy black glass with low iron content and preparation method thereof

Privacy black glass was prepared by mixing a low-iron content formula and a multi-component colorant using the float glass production process. This solved the problems of poor heat transmission and difficult melting in the production of black glass, achieving an aesthetically pleasing neutral black color and excellent heat insulation and energy-saving functions.

CN121377527APending Publication Date: 2026-01-23WEIHAI BLUE STAR GLASS HLDG CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411179002.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

In existing black glass production technology, the use of iron oxide as a colorant results in poor heat permeability of the glass melt, difficulty in melting, and poor production stability. Furthermore, the addition of coal powder affects the gloss.

Method used

Using a low-iron-content formula, privacy black glass is prepared by utilizing the mixed coloring effect of multiple colorants such as Fe2O3, Cr2O3, NiO, CoO, and Se through float glass production process, achieving complementary absorption colors and obtaining a pure neutral black color.

Benefits of technology

It achieves a beautiful and sophisticated neutral black effect, solves the problems of poor heat permeability and difficulty in melting, and has ultra-low visible light transmittance, ultraviolet blocking ability, and excellent sunlight control and heat insulation and energy saving functions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005011553200000011
    Figure BDA0005011553200000011
  • Figure BDA0005011553200000021
    Figure BDA0005011553200000021
  • Figure BDA0005011553200000022
    Figure BDA0005011553200000022
Patent Text Reader

Abstract

The invention discloses privacy black glass with low iron content and a preparation method thereof.The privacy black glass is prepared from, by mass, 69%-74% of SiO2, 12%-16% of Na2O, 8%-12% of CaO, 3%-7% of MgO, 0.5%-2% of Al2O3, 0.3%-1% of Fe2O3, 0.05%-0.5% of Cr2O3, 0.05%-0.3% of NiO, 0.02%-0.08% of CoO, 0.02%-0.08% of Se and 0.1%-0.5% of SnO2, all the raw materials are weighed according to the converted proportion of the glass components, and the privacy black glass with the low iron content is prepared through a series of process steps of batch mixing, melting, forming, annealing and the like. The product provided by the invention can be prepared; the component proportion of the black glass solves the problems of poor diathermancy and difficult melting of molten glass caused by high iron content, and the black glass prepared by the method disclosed by the invention is pure and neutral in color, has excellent sunlight control function, heat insulation and energy saving effects and privacy protection function, and can be used in the fields of high-grade automobile sunroofs / side windows, household appliance panels, high-end buildings, home decoration and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new glass materials technology, and in particular to a privacy black glass with low iron content and its preparation process. Background Technology

[0002] Black glass, also known as tinted glass, has a strong ability to absorb sunlight and has extremely low visible light transmittance and ultraviolet transmittance. It offers excellent sunlight control, heat insulation and energy-saving performance, as well as privacy protection. The glass also boasts a beautiful and sophisticated appearance, making it widely used in high-end automotive sunroofs / side windows, appliance panels, high-end buildings, and home decoration.

[0003] Generally, black glass is made by adding a certain amount of colorant to ordinary glass components. Due to the light absorption of the colorant, the glass appears black. However, the current production of black glass has the following problems: 1) Some black glass production technologies require the addition of coal powder to the glass, which affects the gloss of the black glass; 2) Some black glass production technologies use a large amount of iron oxide as a colorant to achieve a black effect, but due to the strong absorption effect of iron oxide, the heat permeability of the glass melt deteriorates, resulting in a large temperature gradient in the depth of the melting furnace, causing melting difficulties and crystallization. Frozen material is prone to occur in the feeding area, the melting process is complex, difficult to control, and the production stability is not ideal. Summary of the Invention

[0004] To address the aforementioned issues, this invention provides a privacy black glass with low iron content (Fe2O3% < 1) and its preparation method. Using conventional float glass production processes and equipment, a pure black privacy glass with low transparency, heat insulation, and ultraviolet blocking function can be prepared.

[0005] To achieve the above-mentioned objectives, the present invention adopts the following technical solution:

[0006] This invention provides a privacy black glass with low iron content, referred to as black glass, whose composition by mass percentage is as follows:

[0007]

[0008]

[0009] The privacy black glass uses SiO2 as the primary component forming the glass structure, with silicon-oxygen tetrahedral structural units forming the glass's "skeleton." Na2O acts as an external network oxide, breaking up the network, reducing the viscosity of the molten glass, and lowering its melting temperature. CaO acts as a network modifier, accelerating the melting and clarifying process and improving the glass's chemical stability. MgO acts as a network modifier, improving the glass's chemical stability and mechanical strength, and reducing its crystallization tendency. Al2O3 acts as a network intermediate, improving the glass's chemical stability, thermal stability, and mechanical strength. Fe2O3 (FeO) is a colorant with absorption peaks at multiple positions, including... Absorption peaks are observed at wavelengths of 200nm, 225nm, 380nm, 420nm, 435nm, and 1050nm. Cr2O3 is a colorant with absorption peaks at 450nm and 650nm. NiO is a colorant with absorption peaks at 450nm, 560nm, 630nm, 930nm, 1200nm, and 1800nm. CoO is a colorant with absorption peaks at 550nm and 620nm. Se is a colorant with absorption peaks at 425nm and 500nm. SnO2 is an atmosphere conditioner used to regulate the melting atmosphere, maintain a suitable oxidation / reduction atmosphere, and ensure the valence state and coloring effect of the oxides. SiO2, Na2O, CaO, MgO, and Al2O3 are the basic components of glass, forming its structure and physicochemical properties. Fe2O3 (FeO), Cr2O3, NiO, CoO, and Se are colorants. Through the mixed coloring effect of multiple colorants, complementary absorption colors are achieved, resulting in a pure neutral black.

[0010] Preferably, a privacy black glass has the following components by weight percentage:

[0011]

[0012] The privacy black glass is a pure neutral black with a transmission color a* value of 1.2 to 1.8 and a transmission color b* value of -1.5 to -0.8.

[0013] The privacy glass has a visible light transmittance of 0.05–8%, an ultraviolet light transmittance of 0–8%, and a shading coefficient of 0.05–0.45.

[0014] The present invention also proposes a method for preparing the privacy black glass by weighing various raw materials according to the above glass composition and the calculated proportions, and by carrying out a series of process steps such as batch mixing, melting, forming and annealing.

[0015] Includes the following steps:

[0016] (1) Preparation of batch: According to the designed glass composition, weigh various raw materials in proportion, grind and mix them evenly, with a sodium sulfate content of 2-3% and a sodium nitrate content of 1-1.5%.

[0017] (2) Melting: The mixed materials are fed into the melting furnace for melting and clarification. The temperature of the melting section is 1580℃~1620℃, and the temperature of the cooling section is 1120℃~1150℃. An oxygen lance (#0) is added to increase the temperature of the melting zone. A multi-drain cooling bubbler is installed at the bottom of the furnace to accelerate the replacement of the stationary layer at the bottom of the pool and the convection of the molten glass, pushing the cold molten glass at the bottom to rise and improving the uniformity of the molten glass.

[0018] (3) Shaping: The molten and clarified glass liquid flows into the tin bath for shaping to form a glass ribbon. The ratio of the protective gas nitrogen and hydrogen is adjusted, with the hydrogen ratio reduced by 1% to prevent the reduction of oxides such as Cr2O3 and NiO. The temperature of the glass ribbon at the outlet of the tin bath is 600℃~610℃.

[0019] (4) Annealing: The formed glass ribbon is put into the annealing furnace for annealing treatment to complete the production process. Due to the strong heat absorption capacity of black glass and the uneven heat dissipation at the edge, the temperature of zone A of the annealing furnace is increased to 560℃~580℃ to enhance temperature homogenization. The temperature of the glass ribbon leaving the annealing furnace outlet is 60℃~70℃.

[0020] Compared with existing technologies for producing black glass, the advantages of this invention are:

[0021] (1) By utilizing the mixed coloring effect of multi-component colorants, complementary absorption colors are achieved, resulting in a pure neutral black with a beautiful and sophisticated color.

[0022] (2) The low iron content formula is adopted and the melting process is simple. The production requirements can be met by using the conventional float glass production process. It solves the problems of poor heat permeability of glass melt, difficulty in melting, and easy freezing of material in the feeding area caused by high iron content. The production stability is good.

[0023] (3) The glass has an ultra-low visible light transmittance, can block ultraviolet rays, has excellent sunlight control function, heat insulation and energy saving effect, and privacy protection function. Detailed Implementation

[0024] The method of the present invention is further illustrated below with examples.

[0025] Example 1

[0026] This invention provides a privacy black glass with low iron content, the composition of which is as follows:

[0027] Glass composition of Example 1

[0028] Components (wt%) content SiO2 74.0 Na2O 13.4 CaO 8.0 MgO 3.0 Al2O3 0.5 Fe2O3 0.3 NiO 0.3 Cr2O3 0.3 CoO 0.06 Se 0.06 SnO2 0.15

[0029] The privacy black glass uses SiO2 as the primary component forming the glass structure, with silicon-oxygen tetrahedral structural units forming the glass's "skeleton." Na2O acts as an external network oxide, breaking up the network, reducing the viscosity of the molten glass, and lowering its melting temperature. CaO acts as a network modifier, accelerating the melting and clarifying process and improving the glass's chemical stability. MgO acts as a network modifier, improving the glass's chemical stability and mechanical strength, and reducing its crystallization tendency. Al2O3 acts as a network intermediate, improving the glass's chemical stability, thermal stability, and mechanical strength. Fe2O3 (FeO) is a colorant with absorption peaks at multiple positions, including... Absorption peaks are observed at wavelengths of 200nm, 225nm, 380nm, 420nm, 435nm, and 1050nm. Cr2O3 is a colorant with absorption peaks at 450nm and 650nm. NiO is a colorant with absorption peaks at 450nm, 560nm, 630nm, 930nm, 1200nm, and 1800nm. CoO is a colorant with absorption peaks at 550nm and 620nm. Se is a colorant with absorption peaks at 425nm and 500nm. SnO2 is an atmosphere conditioner used to regulate the melting atmosphere, maintain a suitable oxidation / reduction atmosphere, and ensure the valence state and coloring effect of the oxides. SiO2, Na2O, CaO, MgO, and Al2O3 are the basic components of glass, forming its structure and physicochemical properties. Fe2O3 (FeO), Cr2O3, NiO, CoO, and Se are colorants. Through the mixed coloring effect of multiple colorants, complementary absorption colors are achieved, resulting in a pure neutral black.

[0030] The present invention also proposes a method for preparing the privacy black glass by weighing various raw materials according to the above glass composition and the calculated proportions, and by carrying out a series of process steps such as batch mixing, melting, forming and annealing.

[0031] The specific implementation steps are as follows:

[0032] (1) Preparation of batch: According to the designed glass composition, weigh various raw materials in proportion, grind and mix them evenly, with a sodium sulfate content of 2% and a sodium nitrate content of 1%;

[0033] (2) Melting: The mixed materials are put into the melting furnace for melting and clarification. The temperature of the melting section is 1580℃ and the temperature of the cooling section is 1120℃. A No. 0 oxygen lance is added to increase the temperature of the melting zone. A multi-drain water cooling bubbler is installed at the bottom of the furnace to accelerate the replacement of the stationary layer at the bottom of the pool and the convection of the glass liquid, push the bottom cold glass liquid to rise, and improve the uniformity of the glass liquid.

[0034] (3) Forming: The molten and clarified glass liquid is poured into the tin bath for forming, creating a glass ribbon. The ratio of the protective gases nitrogen and hydrogen is adjusted, with the hydrogen ratio reduced by 1% to prevent the reduction of oxides such as Cr2O3 and NiO. The temperature of the glass ribbon at the outlet of the tin bath is 600℃.

[0035] (4) Annealing: The formed glass ribbon is put into the annealing furnace for annealing treatment to complete the production process; due to the strong heat absorption capacity of black glass and uneven heat dissipation at the edge, the temperature of zone A of the annealing furnace is increased to 560℃ to enhance temperature homogenization, and the temperature of the glass ribbon leaving the annealing furnace outlet is 60℃.

[0036] Through the above steps and by using a mixture of colorants such as Fe2O3 (FeO), Cr2O3, NiO, CoO, and Se to achieve complementary absorption colors, a pure neutral black privacy glass is prepared.

[0037] Compared with existing technologies for producing black glass, the advantages of this invention are:

[0038] (1) By utilizing the mixed coloring effect of multi-component colorants, complementary absorption colors are achieved, resulting in a pure neutral black with a beautiful and sophisticated color.

[0039] (2) The low iron content formula is adopted and the melting process is simple. The production requirements can be met by using the conventional float glass production process. It solves the problems of poor heat permeability of glass melt, difficulty in melting, and easy freezing of material in the feeding area caused by high iron content. The production stability is good.

[0040] (3) The glass has an ultra-low visible light transmittance, can block ultraviolet rays, has excellent sunlight control function, heat insulation and energy saving effect, and privacy protection function.

[0041] The properties of the prepared glass are as follows:

[0042] Performance parameters of black glass in Example 1

[0043] Performance indicators data Glass thickness (mm) 4 Transmission a* 1.2 Transmission b* -0.8 Visible light transmittance % 8.0 UV transmittance % 8.0 Shading coefficient 0.45

[0044] Example 2

[0045] This invention provides a privacy black glass with low iron content, the composition of which is as follows:

[0046] Glass composition of Example 2

[0047]

[0048]

[0049] The privacy black glass uses SiO2 as the primary component forming the glass structure, with silicon-oxygen tetrahedral structural units forming the glass's "skeleton." Na2O acts as an external network oxide, breaking up the network, reducing the viscosity of the molten glass, and lowering its melting temperature. CaO acts as a network modifier, accelerating the melting and clarifying process and improving the glass's chemical stability. MgO acts as a network modifier, improving the glass's chemical stability and mechanical strength, and reducing its crystallization tendency. Al2O3 acts as a network intermediate, improving the glass's chemical stability, thermal stability, and mechanical strength. Fe2O3 (FeO) is a colorant with absorption peaks at multiple positions, including... Absorption peaks are observed at wavelengths of 200nm, 225nm, 380nm, 420nm, 435nm, and 1050nm. Cr2O3 is a colorant with absorption peaks at 450nm and 650nm. NiO is a colorant with absorption peaks at 450nm, 560nm, 630nm, 930nm, 1200nm, and 1800nm. CoO is a colorant with absorption peaks at 550nm and 620nm. Se is a colorant with absorption peaks at 425nm and 500nm. SnO2 is an atmosphere conditioner used to regulate the melting atmosphere, maintain a suitable oxidation / reduction atmosphere, and ensure the valence state and coloring effect of the oxides. SiO2, Na2O, CaO, MgO, and Al2O3 are the basic components of glass, forming its structure and physicochemical properties. Fe2O3 (FeO), Cr2O3, NiO, CoO, and Se are colorants. Through the mixed coloring effect of multiple colorants, complementary absorption colors are achieved, resulting in a pure neutral black.

[0050] The present invention also proposes a method for preparing the privacy black glass by weighing various raw materials according to the above glass composition and the calculated proportions, and by carrying out a series of process steps such as batch mixing, melting, forming and annealing.

[0051] The specific implementation steps are as follows:

[0052] (1) Preparation of batch: According to the designed glass composition, weigh various raw materials in proportion, grind and mix them evenly, with a sodium sulfate content of 3% and a sodium nitrate content of 1.5%.

[0053] (2) Melting: The mixed materials are fed into the melting furnace for melting and clarification. The melting section temperature is 1620℃, and the cooling section temperature is 1150℃. An oxygen lance (#0) is added to increase the temperature of the melting zone. A multi-stage water-cooled bubbler is installed at the bottom of the furnace to accelerate the replacement of the stationary layer at the bottom of the tank and the convection of the molten glass, pushing the cold molten glass at the bottom to rise and improving the uniformity of the molten glass.

[0054] (3) Shaping: The molten and clarified glass liquid flows into the tin bath for shaping to form a glass ribbon. The ratio of the protective gases nitrogen and hydrogen is adjusted, with the hydrogen ratio reduced by 1% to prevent the reduction of oxides such as Cr2O3 and NiO. The temperature of the glass ribbon at the outlet of the tin bath is 610℃.

[0055] (4) Annealing: The formed glass ribbon enters the annealing furnace for annealing treatment to complete the production process. Due to the strong heat absorption capacity of black glass and uneven heat dissipation at the edge, the temperature of zone A of the annealing furnace is increased to 580℃ to enhance temperature homogenization. The temperature of the glass ribbon leaving the annealing furnace outlet is 70℃.

[0056] Through the above steps and the mixed coloring effect of multiple colorants such as Fe2O3 (FeO), Cr2O3, NiO, CoO, and Se, complementary absorption colors are achieved, thereby producing pure neutral black privacy glass.

[0057] Compared with the prior art, the beneficial effects of the present invention are:

[0058] (1) By utilizing the mixed coloring effect of multi-component colorants, complementary absorption colors are achieved, resulting in a pure neutral black with a beautiful and sophisticated color.

[0059] (2) The low iron content formula is adopted and the melting process is simple. The production requirements can be met by using the conventional float glass production process. It solves the problems of poor heat permeability of glass melt, difficulty in melting, and easy freezing of material in the feeding area caused by high iron content. The production stability is good.

[0060] (3) The glass has an ultra-low visible light transmittance, can block ultraviolet rays, has excellent sunlight control function, heat insulation and energy saving effect, and privacy protection function.

[0061] The performance parameters of the prepared glass are as follows.

[0062] Performance parameters of black glass in Example 2

[0063]

[0064]

[0065] Example 3

[0066] This invention provides a privacy black glass with low iron content, the composition of which is as follows:

[0067] Glass composition of Example 3

[0068] Components (wt%) content SiO2 70.1 Na2O 12.8 CaO 8.4 MgO 7.0 Al2O3 0.6 Fe2O3 0.76 NiO 0.15 Cr2O3 0.5 CoO 0.04 Se 0.04 SnO2 0.26

[0069] The privacy black glass uses SiO2 as the primary component forming the glass structure, with silicon-oxygen tetrahedral structural units forming the glass's "skeleton." Na2O acts as an external network oxide, breaking up the network, reducing the viscosity of the molten glass, and lowering its melting temperature. CaO acts as a network modifier, accelerating the melting and clarifying process and improving the glass's chemical stability. MgO acts as a network modifier, improving the glass's chemical stability and mechanical strength, and reducing its crystallization tendency. Al2O3 acts as a network intermediate, improving the glass's chemical stability, thermal stability, and mechanical strength. Fe2O3 (FeO) is a colorant with absorption peaks at multiple positions, including... Absorption peaks are observed at wavelengths of 200nm, 225nm, 380nm, 420nm, 435nm, and 1050nm. Cr2O3 is a colorant with absorption peaks at 450nm and 650nm. NiO is a colorant with absorption peaks at 450nm, 560nm, 630nm, 930nm, 1200nm, and 1800nm. CoO is a colorant with absorption peaks at 550nm and 620nm. Se is a colorant with absorption peaks at 425nm and 500nm. SnO2 is an atmosphere conditioner used to regulate the melting atmosphere, maintain a suitable oxidation / reduction atmosphere, and ensure the valence state and coloring effect of the oxides. SiO2, Na2O, CaO, MgO, and Al2O3 are the basic components of glass, forming its structure and physicochemical properties. Fe2O3 (FeO), Cr2O3, NiO, CoO, and Se are colorants. Through the mixed coloring effect of multiple colorants, complementary absorption colors are achieved, resulting in a pure neutral black.

[0070] The present invention also proposes a method for preparing the privacy black glass by weighing various raw materials according to the above glass composition and the calculated proportions, and by carrying out a series of process steps such as batch mixing, melting, forming and annealing.

[0071] The specific implementation steps are as follows:

[0072] (1) Preparation of the batch: According to the designed glass composition, weigh the various raw materials in proportion, and grind and mix them evenly. The content of Glauber's salt is 2.5%, and the amount of sodium nitrate is 1.25%.

[0073] (2) Melting: The mixed materials are fed into the melting furnace for melting and clarification. The melting section temperature is 1600℃, and the cooling section temperature is 1135℃. An oxygen lance (#0) is added to increase the temperature of the melting zone. A multi-stage water-cooled bubbler is installed at the bottom of the furnace to accelerate the replacement of the stationary layer at the bottom of the tank and the convection of the molten glass, pushing the cold molten glass at the bottom to rise and improving the uniformity of the molten glass.

[0074] (3) Shaping: The molten and clarified glass liquid flows into the tin bath for shaping, forming a glass ribbon. The ratio of the protective gases nitrogen and hydrogen is adjusted, with the hydrogen ratio reduced by 1% to prevent the reduction of oxides such as Cr2O3 and NiO. The temperature of the glass ribbon at the outlet of the tin bath is 605℃.

[0075] (4) Annealing: The formed glass ribbon is placed into the annealing furnace for annealing treatment to complete the production process. Due to the strong heat absorption capacity of black glass and the uneven heat dissipation at the edges, the temperature of zone A of the annealing furnace is increased to 570℃ to enhance temperature homogenization. The temperature of the glass ribbon leaving the annealing furnace outlet is 65℃.

[0076] Through the above steps and the mixed coloring effect of multiple colorants such as Fe2O3 (FeO), Cr2O3, NiO, CoO, and Se, complementary absorption colors are achieved, thereby producing pure neutral black privacy glass.

[0077] Compared with the prior art, the beneficial effects of the present invention are:

[0078] (1) By utilizing the mixed coloring effect of multi-component colorants, complementary absorption colors are achieved, resulting in a pure neutral black with a beautiful and sophisticated color.

[0079] (2) The low iron content formula is adopted and the melting process is simple. The production requirements can be met by using the conventional float glass production process. It solves the problems of poor heat permeability of glass melt, difficulty in melting, and easy freezing of material in the feeding area caused by high iron content. The production stability is good.

[0080] (3) The glass has an ultra-low visible light transmittance, can block ultraviolet rays, has excellent sunlight control function, heat insulation and energy saving effect, and privacy protection function.

[0081] The performance parameters of the prepared glass are as follows.

[0082] Performance parameters of black glass in Example 3

[0083] Performance indicators numerical values Glass thickness (mm) 6 Transmission a* 1.6 Transmission b* -1.3 Visible light transmittance % 2.1 UV transmittance % 0.02 Shading coefficient 0.24

[0084] Example 4

[0085] This invention provides a privacy black glass with low iron content, the composition of which is as follows:

[0086] Glass composition of Example 4

[0087]

[0088]

[0089] The privacy black glass uses SiO2 as the primary component forming the glass structure, with silicon-oxygen tetrahedral structural units forming the glass's "skeleton." Na2O acts as an external network oxide, breaking up the network, reducing the viscosity of the molten glass, and lowering its melting temperature. CaO acts as a network modifier, accelerating the melting and clarifying process and improving the glass's chemical stability. MgO acts as a network modifier, improving the glass's chemical stability and mechanical strength, and reducing its crystallization tendency. Al2O3 acts as a network intermediate, improving the glass's chemical stability, thermal stability, and mechanical strength. Fe2O3 (FeO) is a colorant with absorption peaks at multiple positions, including... Absorption peaks are observed at wavelengths of 200nm, 225nm, 380nm, 420nm, 435nm, and 1050nm. Cr2O3 is a colorant with absorption peaks at 450nm and 650nm. NiO is a colorant with absorption peaks at 450nm, 560nm, 630nm, 930nm, 1200nm, and 1800nm. CoO is a colorant with absorption peaks at 550nm and 620nm. Se is a colorant with absorption peaks at 425nm and 500nm. SnO2 is an atmosphere conditioner used to regulate the melting atmosphere, maintain a suitable oxidation / reduction atmosphere, and ensure the valence state and coloring effect of the oxides. SiO2, Na2O, CaO, MgO, and Al2O3 are the basic components of glass, forming its structure and physicochemical properties. Fe2O3 (FeO), Cr2O3, NiO, CoO, and Se are colorants. Through the mixed coloring effect of multiple colorants, complementary absorption colors are achieved, resulting in a pure neutral black.

[0090] The present invention also proposes a method for preparing the privacy black glass by weighing various raw materials according to the above glass composition and the calculated proportions, and by carrying out a series of process steps such as batch mixing, melting, forming and annealing.

[0091] The specific implementation steps are as follows:

[0092] (1) Preparation of raw materials. According to the designed glass composition, weigh all raw materials in proportion, and grind and mix them evenly. The content of Glauber's salt is 2.3%, and the amount of sodium nitrate is 1.15%.

[0093] (2) Melting. The mixed materials are fed into the melting furnace for melting and clarification. The temperature of the melting section is 1595℃, and the temperature of the cooling section is 1130℃. An oxygen lance (#0) is added to increase the temperature of the melting zone. A multi-stage water-cooled bubbler is installed at the bottom of the furnace to accelerate the replacement of the stationary layer at the bottom of the pool and the convection of the molten glass, pushing the cold molten glass at the bottom to rise and improving the uniformity of the molten glass.

[0094] (3) Shaping. The molten and clarified glass liquid is poured into the tin bath for shaping to form a glass ribbon. The ratio of the protective gases nitrogen and hydrogen is adjusted, with the hydrogen ratio reduced by 1% to prevent the reduction of oxides such as Cr2O3 and NiO. The temperature of the glass ribbon at the outlet of the tin bath is 602℃.

[0095] (4) Annealing. The formed glass ribbon is placed into an annealing furnace for annealing treatment to complete the production process. Due to the strong heat absorption capacity of black glass and uneven heat dissipation at the edges, the temperature of zone A in the annealing furnace is increased to 572℃ to enhance temperature homogenization. The temperature of the glass ribbon leaving the annealing furnace outlet is 66℃.

[0096] Through the above steps and the mixed coloring effect of multiple colorants such as Fe2O3 (FeO), Cr2O3, NiO, CoO, and Se, complementary absorption colors are achieved, thereby producing pure neutral black privacy glass.

[0097] Compared with the prior art, the beneficial effects of the present invention are:

[0098] (1) By utilizing the mixed coloring effect of multi-component colorants, complementary absorption colors are achieved, resulting in a pure neutral black with a beautiful and sophisticated color.

[0099] (2) The low iron content formula is adopted and the melting process is simple. The production requirements can be met by using the conventional float glass production process. It solves the problems of poor heat permeability of glass melt, difficulty in melting, and easy freezing of material in the feeding area caused by high iron content. The production stability is good.

[0100] (3) The glass has an ultra-low visible light transmittance, can block ultraviolet rays, has excellent sunlight control function, heat insulation and energy saving effect, and privacy protection function.

[0101] The properties of the prepared glass are as follows:

[0102] Performance parameters of black glass in Example 4

[0103] Performance indicators numerical values Glass thickness (mm) 8 Transmission a* 1.7 Transmission b* -1.4 Visible light transmittance % 0.6 UV transmittance % 0 Shading coefficient 0.12

[0104] Example 5

[0105] This invention provides a privacy black glass with low iron content, the composition of which is as follows:

[0106] Glass composition of Example 5

[0107] Components (wt%) content SiO2 72.2 Na2O 14.1 CaO 8.4 MgO 3.2 Al2O3 0.6 <![CDATA[Fe2O3]]> 0.72 NiO 0.25 <![CDATA[Cr2O3]]> 0.10 CoO 0.045 Se 0.045 <![CDATA[SnO2]]> 0.5

[0108] The privacy black glass uses SiO2 as the primary component forming the glass structure, with silicon-oxygen tetrahedral structural units forming the glass's "skeleton." Na2O acts as an external network oxide, breaking up the network, reducing the viscosity of the molten glass, and lowering its melting temperature. CaO acts as a network modifier, accelerating the melting and clarifying process and improving the glass's chemical stability. MgO acts as a network modifier, improving the glass's chemical stability and mechanical strength, and reducing its crystallization tendency. Al2O3 acts as a network intermediate, improving the glass's chemical stability, thermal stability, and mechanical strength. Fe2O3 (FeO) is a colorant with absorption peaks at multiple positions, including... Absorption peaks are observed at wavelengths of 200nm, 225nm, 380nm, 420nm, 435nm, and 1050nm. Cr2O3 is a colorant with absorption peaks at 450nm and 650nm. NiO is a colorant with absorption peaks at 450nm, 560nm, 630nm, 930nm, 1200nm, and 1800nm. CoO is a colorant with absorption peaks at 550nm and 620nm. Se is a colorant with absorption peaks at 425nm and 500nm. SnO2 is an atmosphere conditioner used to regulate the melting atmosphere, maintain a suitable oxidation / reduction atmosphere, and ensure the valence state and coloring effect of the oxides. SiO2, Na2O, CaO, MgO, and Al2O3 are the basic components of glass, forming its structure and physicochemical properties. Fe2O3 (FeO), Cr2O3, NiO, CoO, and Se are colorants. Through the mixed coloring effect of multiple colorants, complementary absorption colors are achieved, resulting in a pure neutral black.

[0109] The present invention also proposes a method for preparing the privacy black glass by weighing various raw materials according to the above glass composition and the calculated proportions, and by carrying out a series of process steps such as batch mixing, melting, forming and annealing.

[0110] The specific implementation steps are as follows:

[0111] (1) Preparation of raw materials. According to the designed glass composition, weigh all raw materials in proportion, and grind and mix them evenly. The content of Glauber's salt is 2.65%, and the amount of sodium nitrate is 1.45%.

[0112] (2) Melting. The mixed materials are fed into the melting furnace for melting and clarification. The temperature of the melting section is 1610℃, and the temperature of the cooling section is 1142℃. An oxygen lance (#0) is added to increase the temperature of the melting zone. A multi-stage water-cooled bubbler is installed at the bottom of the furnace to accelerate the replacement of the stationary layer at the bottom of the pool and the convection of the molten glass, pushing the cold molten glass at the bottom to rise and improving the uniformity of the molten glass.

[0113] (3) Shaping. The molten and clarified glass liquid is poured into the tin bath for shaping, forming a glass ribbon. The ratio of the protective gases nitrogen and hydrogen is adjusted, with the hydrogen ratio reduced by 1% to prevent the reduction of oxides such as Cr2O3 and NiO. The temperature of the glass ribbon at the outlet of the tin bath is 608℃.

[0114] (4) Annealing. The formed glass ribbon is placed into an annealing furnace for annealing treatment to complete the production process. Due to the strong heat absorption capacity of black glass and uneven heat dissipation at the edges, the temperature of zone A in the annealing furnace is increased to 575℃ to enhance temperature homogenization. The temperature of the glass ribbon leaving the annealing furnace outlet is 67℃.

[0115] Through the above steps and the mixed coloring effect of multiple colorants such as Fe2O3 (FeO), Cr2O3, NiO, CoO, and Se, complementary absorption colors are achieved, thereby producing pure neutral black privacy glass.

[0116] Compared with the prior art, the beneficial effects of the present invention are:

[0117] (1) By utilizing the mixed coloring effect of multi-component colorants, complementary absorption colors are achieved, resulting in a pure neutral black with a beautiful and sophisticated color.

[0118] (2) The low iron content formula is adopted and the melting process is simple. The production requirements can be met by using the conventional float glass production process. It solves the problems of poor heat permeability of glass melt, difficulty in melting, and easy freezing of material in the feeding area caused by high iron content. The production stability is good.

[0119] (3) The glass has an ultra-low visible light transmittance, can block ultraviolet rays, has excellent sunlight control function, heat insulation and energy saving effect, and privacy protection function.

[0120] The properties of the prepared glass are as follows:

[0121] Performance parameters of black glass in Example 5

[0122] Performance indicators numerical values Glass thickness (mm) 12 Transmission a* 1.8 Transmission b* -1.5 Visible light transmittance % 0.05 UV transmittance % 0 Shading coefficient 0.05

[0123] It should be noted that the above embodiments only illustrate some implementation methods of the present invention and are not intended to limit the present invention in any way. Even for those skilled in the art or patent practitioners, several modifications and improvements can be made based on the concept of the present invention, but all of them will fall within the protection scope of the present invention.

Claims

1. A privacy black glass with low iron content, characterized in that, By mass percentage, the glass composition is as follows: SiO2 69–74%, Na2O 12–16%, CaO 8–12%, MgO 3–7%, Al2O3 0.5–2%, Fe2O3 0.3–1%, Cr2O3 0.05–0.5%, NiO 0.05–0.3%, CoO 0.02–0.08%, Se 0.02–0.08%, and SnO2 0.1–0.5%.

2. The privacy black glass with low iron content according to claim 1, characterized in that... The glass composition is as follows: SiO2 69–74%, Na2O 12–16%, CaO 8–12%, MgO 3–7%, Al2O3 0.5–2%, Fe2O3 0.3–1%, Cr2O3 0.1–0.3%, NiO 0.1–0.25%, CoO 0.04–0.06%, Se 0.04–0.06%, and SnO2 0.15–0.3%.

3. The privacy black glass with low iron content according to claim 1, characterized in that... The privacy black glass is a pure neutral black with a transmission color a* value of 1.2 to 1.8 and a transmission color b* value of -1.5 to -0.

8.

4. The privacy black glass with low iron content according to claim 1, characterized in that... The privacy glass has a visible light transmittance of 0.05–8%, an ultraviolet light transmittance of 0–8%, and a shading coefficient of 0.05–0.

45.

5. A method for preparing privacy black glass with low iron content, characterized in that, Includes the following steps: (1) Preparation of batch: Weigh various raw materials according to the proportion of the black glass components, grind and mix them evenly, with a sodium sulfate content of 2-3% and a sodium nitrate content of 1-1.5%; (2) Melting: The mixed materials are put into the melting furnace for melting and clarification. The temperature of the melting section is 1580℃~1620℃ and the temperature of the cooling section is 1120℃~1150℃. A No. 0 oxygen lance is added to increase the temperature of the melting zone. A multi-drain water cooling bubbler is installed at the bottom of the furnace to accelerate the replacement of the stationary layer at the bottom of the pool and the convection of the glass liquid, push the bottom cold glass liquid to rise, and improve the uniformity of the glass liquid. (3) Forming: The molten and clear glass liquid flows into the tin bath for forming to form a glass ribbon. The ratio of protective gas nitrogen and hydrogen is adjusted. The hydrogen ratio is reduced by 1% to prevent oxides such as Cr2O3 and NiO from being reduced. The temperature of the glass ribbon at the outlet of the tin bath is 600℃~610℃. (4) Annealing: The formed glass ribbon is put into the annealing furnace for annealing treatment. The temperature of zone A of the annealing furnace is increased to 560℃~580℃ to enhance temperature homogenization. The temperature of the glass ribbon leaving the annealing furnace outlet is 60℃~70℃. Through the above steps and the mixed coloring effect of multi-component colorants such as Fe2O3 (FeO), Cr2O3, NiO, CoO, and Se, complementary absorption colors are achieved, thereby producing pure neutral black privacy glass.

Citation Information

Patent Citations

  • Low-light-transmission privacy energy-saving float glass composition and preparation method thereof

    CN107117811A

  • Black glass and preparation method thereof

    CN111302624A

  • Float color glass as well as preparation method and application thereof

    CN116969674A

  • Grey secret glass with strong ultraviolet and infrared absorption

    CN1636908A

  • Dark grey soda-lime-silica glass composition which is intended for the production of glazing

    CN1956930A